Faking on personality assessments in high-stakes settings: A critical review - Dunlop, Patrick; Xia, Mengting; Anglim, J. (Elsevier, 2025)
Faking—deliberately self-presenting in an overly favorable light—is a persistent challenge for personality assessments in high-stakes contexts such as personnel selection. This review examines recent research on the impact of faking, strategies for its prevention and detection, and future directions. Meta-analytic evidence supports the theory of validity declines from faking, but meaningful predictive utility remains. Research on prevention has grown, covering approaches such as forced-choice formats, neutralized items, warnings, gamified, and implicit measures. However, many methods involve practical or psychometric trade-offs. Although the literature is substantial, we encourage research involving larger samples, real applicants, and within-subjects designs. Finally, novel assessment methods, including those using generative artificial intelligence, warrant further investigation both as potential solutions and as tools for faking.